Sterwe, dood en rou as 'n gesondheidsprobleem - Frederika M.J. de Villiers (AOSIS, 1979)
It is clear that the progress in medical technology, the increasing awareness of psycho - social aspects in the health services, the humanistic emphasis on patient care, changes in the family structure, the hospitalisation of the dying patient and the increasing relationship of the health personnel in the death situation, all resulted in an increasing idenitification with dying, death and mourning as health care problems. These tendencies have reached a level which created a need for the development of effective approaches in respect of the case of man in the throes of death. The acceptance of the responsibility not only for the care but also for the accompaniment of dying persons and their loved ones, has become a necessity, because dying, death and mourning actually are health problems.